ANALISIS INDUSTRI BATIK DI INDONESIA (Fokus Ekonomi, 2008)
One of the popular fashions in Indonesia is batik. Several countries had acknowledgedthat batik was originated from their countries. In fact, Malaysia had registered a patent for batik.However, recently UNESCO has acknowledged that batik is indeed an Indonesian culturalheritage. In Indonesia, batik has developed since the beginning of the 19th century and hasundergone the rise and fall through its development.The analysis of batik industry will identify the opportunities and strengths of Indonesianbatik industry in facing competition. In addition, it also will identify threats and weaknesses ofbatik industry using SWOT analysis.Prior to analyzing opportunities, strengths, threats and weaknesses of batik industry, themacro environment of the company is analyzed that consist of technology, general economiccondition, legislation and regulation, societal values and lifestyle, population demographics. Thestructure of batik industry is also analyzed.Key words: batik industry, opportunities, strength, threats, weaknesses